الرغبة المقاولاتية والإبداع الدى الشباب الجامعي - بومناد, سيف الدين; سنوساوي, عكاشة بشير (جامعة الوادي - University of Eloued, 2019)
تهدف هذه الدراسة إلى تحليل علاقة وأثر التعليم الجامعي على القدرة المقاولاتية والسلوك المقاولاتي الدفع لإنشاء مؤسسة، وتحليل هذه العلاقة من خلال خاصية القدرة على الإبداع لدى الشباب الجامعي بالمقارنة مع الشباب غير الجامعي، واعتمدت الدراسة على اختيار عينة عرضية من مراكز التسهيل ومشاتل المؤسسات ومكاتب التوظيف، وهذا لمقارنة الراغبين في إنشاء مؤسسة بغيرهم في ما يخص القدرة على الإبداع، وقدرت عينة الدراسة بـ 157 شاب. وقد تم جمع البيانات باستعمال الاستبيان الذي صمم بهدف دراسة خصائص الفرد والقدرة على الإبداع بالإضافة إلى الرغبة في إنشاء مؤسسة، ومن أهم النتائج التي خلصت إليها الدراسة دلالة الفروق بين الشباب الجامعي وغير الجامعي في ما يخص القدرة على الإبداع لصالح الشباب الجامعي من جهة، ودلالة الفروق بين الشباب الراغب في إنشاء مؤسسة وغيرهم في ما يخص القدرة على الإبداع لصالح الراغبين في إنشاء مؤسسة. This study aims to highlight the impact of university education on the entrepreneurial intention that motivates the creation of the business, this relationship that requires first and foremost the ability of creativity in young people, in order to carry out this research we have opted for a comparative method between young people from university education compared to other young people in terms of the ability to be creative, and young people who have entrepreneurial intention to others who do not have this intention in terms of their creative capacity, our sample consisted of 157 young people, this study resulted in significant differences between university students and others in their ability to be creative, and young people who already have entrepreneurial intent in their ability to start a business, so the university plays a key role in the transition of Algerian youth from entrepreneurial intent to entrepreneurial action
مقال
Keywords: المقاولاتية ; الإبداع ; الشباب الجامعي